Empirical Equation of Tight Binding Model Parameter to Calculate Bandgap of Semiconducting Single Wall Carbon Nanotube (Journal of Electrical Engineering, 2012)
Both Mod 1 and Mod 2 type Semiconducting single wall carbon nanotubes over a wide diameter range are studied separately to find their band gap trend. For accurate calculation of their band gaps, modification of nearest-neighbor hopping parameter of the tight-binding model is proposed by considering it as a function of nanotube chiral index and mod value. A simple empirical equation for the nearest-neighbor hopping parameter is presented to produce band gaps of these nanotubes that agree well with simulated data. Empirical data are also compared with experimental data and found to be in excellent agreement with it after adding a flat correction.Journal of Electrical Engineering The Institution of Engineers, Bangladesh Vol. EE 37, No. II, December, 2011